The Meaning of Work among Elderly Informal Workers in Sekotong, Indonesia - Maya Atri Komalasari; Moh Taqiuddin; Azhari Evendi; Aliya Rahmawati; Ikrima Fina Hayati (Universitas Muhammadiyah Surakarta, 2026)
The elderly experience a dual vulnerability as both older adults and informal workers; nonetheless, they continue to choose to work. This study aims to uncover the meaning behind the decision to work among elderly informal workers in Sekotong, West Nusa Tenggara. The research is examined utilizing Schutz’s motive theory and the concept of role. Employing a qualitative phenomenological method, data were collected through in-depth interviews, observation, and documentation. Informants were selected purposively, and data analysis was conducted using phenomenological techniques. The results indicate that the meaning behind the elderly’s decision to work is shaped by their perspectives on the aspects of working, alongside the concepts of the